Neurological, psychiatric, and developmental disorders : meeting the challenge in the developing world (National Academy Press, 2001)
Brain disorders neurological, psychiatric, and developmental now affect at least 250 million people in the developing world, and this number is expected to rise as life expectancy increases. Yet public and private health systems in developing countries have paid relatively little attention to brain disorders. The negative attitudes, prejudice, and stigma that often surround many of these disorders have contributed to this neglect. Lacking proper diagnosis and treatment, millions of individual lives are lost to disability and death. Such conditions exact both personal and economic costs on families, communities, and nations. The report describes the causes and risk factors associated with brain disorders. It focuses on six representative brain disorders that are prevalent in developing countries: developmental disabilities, epilepsy, schizophrenia, bipolar disorder, depression, and stroke. The report makes detailed recommendations of ways to reduce the toll exacted by these six disorders. In broader strokes, the report also proposes six major strategies toward reducing the overall burden of brain disorders in the developing world.